Монгол Улсын Гадаад явдлын яамны дөрөв дэх сайд Санжийн Гиваабалжир гэж хэн бэ? - Д, Доржготов (Journal of International Studies, 2009)
English title: Who is Givaabaljir Sanj the 4th Mongolian minister of Foreign Affairs?